2010
DOI: 10.1121/1.3453764
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous auditory nerve activity in the carboplatin-chinchilla model of auditory neuropathy

Abstract: Two hallmark features of auditory neuropathy (AN) are normal outer hair cell function in the presence of an absent/abnormal auditory brainstem response (ABR). Studies of human AN patients are unable to determine whether disruption of the ABR is the result of a reduction of neural input, a loss of auditory nerve fiber (ANF) synchrony, or both. Neurophysiological data from the carboplatin model of AN reveal intact neural synchrony in the auditory nerve and inferior colliculus, despite significant reductions in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Given that neural timing is suggested to reflect temporal jitter and synchronicity, these non-delayed latencies seen in the experimental group after hearing aid use could be interpreted as an increase in synchronicity and may be affected by an inhibition-mediated decrease in temporal jitter. Reduced input from the periphery due to hearing loss, changes neural responses in the inferior colliculus (Cowper-Smith et al, 2010). Reduced afferent neural transmission may be sufficient to desynchronize neural activity in the inferior colliculus and these reductions may destabilize the tight regulation of excitatory/inhibitory neurotransmission needed for temporal processing.…”
Section: Discussionmentioning
confidence: 99%
“…Given that neural timing is suggested to reflect temporal jitter and synchronicity, these non-delayed latencies seen in the experimental group after hearing aid use could be interpreted as an increase in synchronicity and may be affected by an inhibition-mediated decrease in temporal jitter. Reduced input from the periphery due to hearing loss, changes neural responses in the inferior colliculus (Cowper-Smith et al, 2010). Reduced afferent neural transmission may be sufficient to desynchronize neural activity in the inferior colliculus and these reductions may destabilize the tight regulation of excitatory/inhibitory neurotransmission needed for temporal processing.…”
Section: Discussionmentioning
confidence: 99%
“…The chinchilla model has recently been used to test the hypothesis that reduced input from the periphery changes temporal responses of neurons in the inferior colliculus (Cowper-Smith et al, 2010). In the chinchilla, experimental treatment with carboplatin produces inner hair cell loss accompanied by loss of auditory nerve fibers and reduced spike rates of surviving fibers (Wake et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In the chinchilla, experimental treatment with carboplatin produces inner hair cell loss accompanied by loss of auditory nerve fibers and reduced spike rates of surviving fibers (Wake et al, 1994). Cowper-Smith and colleagues (2010) showed that temporal responses of individual auditory nerve fibers and inferior colliculus neurons are similar in chinchilla before and after carboplatin treatment, suggesting that reduced afferent neural transmission is insufficient to desynchronize neural activity in the inferior colliculus, at least over the short term.…”
Section: Discussionmentioning
confidence: 99%
“…This unique pathology was initially reported in the early 1990s; it was hoped that it would produce a model for AN 12 . However, detailed observation failed to show a loss of ANF synchrony in such animals 13 . Gene engineering models have been introduced for selective damage of SGNs.…”
Section: Introductionmentioning
confidence: 87%